Perkembangan Panti Asuhan Muhammadiyah Ketaping Kelurahan Pasar Ambacang Kecamatan Kuranji Padang 1966-2010 - Perdana, Hengki; Kaksim, Kaksim; Meldawati, Meldawati (Pendidikan Sejarah, 2013)
ABSTRAKHengki Perdana ( 08020115 ) : Muhammadiyah Orphanage Ketaping development chief Ambacang Market District Kuranji Field 1966 - 2010 " , essay Educational Studies Program History Social Science Education Department at the High School of Teaching and Educational Studies ( STKIP ) PGRI West Sumatra Padang, 2013         The present study investigates the process of establishment of Muhammadiyah orphanage Ketaping Started by Muhammad Sidiq desire to establish an orphanage because Muhammad Sidiq not have children , so it holds waqf land to build an orphanage. Initial limitation of this study is the year 1966 at the founding of Muhammadiyah Orphanage Ketaping . Final limitation of this writing in 2010 for this status by year Muhammmadiyah Ketaping orphanage suffered under the leadership Abuzar development . method used preformance of this study is the historical method consists of heuristics , criticism , interpretation and historiography .         Based on the research that has been done is known to stand before Ketaping Muhammadiyah orphanage on 18 August 1966. Leadership that is Malin mang koto first , second leader Syoib Ibrahim , leader of the third Syamsuar Abuzar leadership while this experience very rapid growth . Children in the parlor derived from an orphan and waif . Orphanage Darmais cooperate with the Foundation , local government level I and II , federalism , and private enterprises .  Keywords: development Ketaping Muhammadiyah orphanage .